Nilai Pendidikan Karakter Al-Qur’an Surat Ali-Imran Ayat 102-104 Pada Kurikulum Darul Arqam Dasar (DAD) Ikatan Mahasiswa Muhammadiyah (IMM) - Dhian Wahana Putra (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2019)
This study examines values of character education as stated in QS. Ali-Imran verses 102-104 included in the curriculum of Darul Arqam Dasar for Muhammadiyah Student Association (MSA). It should be emphasized that MSA is one of autonomous Muhammadiyah organizations with noble duties and responsibilities. The glory of these responsibilities may be traced through the objectives of MSA—namely: "Striving for Establishing Muslim Academics with Virtuous Morals in Line with the Goals of Muhammadiyah". The selection of QS. Ali-Imran 102-104 as the key value of character education in the curriculum is not without reason, since verse 102 of the surah emphasizes the necessity of believers to pass away as a Muslim. This is in accordance with the spirit of MSA—namely: to construct Muslim academics with noble values. Whereas verse 104 of the letter constitutes a basis for organization, group and bond. This study aims to: 1) examine and describe the concept of character education in the Qur'an surah Ali-Imran verses 102-104, 2) identify the compatibility between the curriculum of Darul Arqam Dasar and MSA with the key value underlying character education based on QS. Ali-Imran verses 102-104. Meanwhile, the method employed a literature study with all the data obtained from books, documents and other written materials.